A sensitive and specific genetically-encoded potassium ion biosensor for in vivo applications across the tree of life - Wu, Sheng-Yi; Wen, Yurong; Serre, Nelson B C; Laursen, Cathrine Charlotte Heiede; Dietz, Andrea Grostøl; Taylor, Brian R; Drobizhev, Mikhail; Molina, Rosana S; Aggarwal, Abhi; Rancic, Vladimir; Becker, Michael; Ballanyi, Klaus; et al. (PLoS biology, 2022)
Potassium ion (K+) plays a critical role as an essential electrolyte in all biological systems. Genetically-encoded fluorescent K+ biosensors are promising tools to further improve our understanding of K+-dependent processes under normal and pathological conditions. Here, we report the crystal structure of a previously reported genetically-encoded fluorescent K+ biosensor, GINKO1, in the K+-bound state. Using structure-guided optimization and directed evolution, we have engineered an improved K+ biosensor, designated GINKO2, with higher sensitivity and specificity. We have demonstrated the utility of GINKO2 for in vivo detection and imaging of K+ dynamics in multiple model organisms, including bacteria, plants, and mice.
Keywords: rezonanční přenos fluorescenční energie; myši; biosenzitivní techniky; Biosensing Techniques; Fluorescence Resonance Energy Transfer; Potassium; ionty; Animals; Mice; Ions; draslík; zvířata